2012
DOI: 10.1371/journal.pone.0031532
|View full text |Cite|
|
Sign up to set email alerts
|

Comparison of Functional Proteomic Analyses of Human Breast Cancer Cell Lines T47D and MCF7

Abstract: T47D and MCF7 are two human hormone-dependent breast cancer cell lines which are widely used as experimental models for in vitro and in vivo (tumor xenografts) breast cancer studies. Several proteins involved in cancer development were identified in these cell lines by proteomic analyses. Although these studies reported the proteomic profiles of each cell line, until now, their differential protein expression profiles have not been established. Here, we used two-dimensional gel and mass spectrometry analyses t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 18 publications
1
23
0
Order By: Relevance
“…Furthermore, activation of the ERβ2 isoform results in ERβ2/ERα heterodimers that are targeted for proteasomal degradation [56]. It is noteworthy, then, that E 2 increases ERβ in T47D but not in MCF-7 or BT-474 [57] and the ER β:α ratio in T47D is reported to be greater than in MCF-7[53], [58] thus, suggesting that cell-specific differences in ER subtypes and other receptors may underlie differential HLA expression in breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, activation of the ERβ2 isoform results in ERβ2/ERα heterodimers that are targeted for proteasomal degradation [56]. It is noteworthy, then, that E 2 increases ERβ in T47D but not in MCF-7 or BT-474 [57] and the ER β:α ratio in T47D is reported to be greater than in MCF-7[53], [58] thus, suggesting that cell-specific differences in ER subtypes and other receptors may underlie differential HLA expression in breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Though statins are known to inhibit cholesterol biosynthesis through mevalonate pathway, they may target multiple proteins regulating different pro survival pathways thereby inhibiting proliferation of cancer cells. Aka et al, recently compared a functional proteome of two hormone-dependent breast cancer cells lines MCF-7 and T47D and the analyses showed that 164 proteins involved in various proliferative functions are differentially expressed between them [8] . Lovastatin induces breast cancer cell death through modulation of E2F1-pathway by altering expression of prohibitin and retinoblastoma (Rb) proteins [9] .…”
Section: Introductionmentioning
confidence: 99%
“…adherent cultured MCF-7 cells. Recently a proteomic analysis has been conducted for MCF-7 monolayer cells in comparison to another commonly used breast cancer cell line T-47D [29]. We believe this to be the first time that the proteome of multiple passages of MCF-7 spheres have been compared to monolayer cells.…”
Section: Discussionmentioning
confidence: 92%